In Silico Identification of Novel Compounds as Anthelmintics Against Haemonchus contortus Through Inhibiting β-Tubulin Isotype 1 and Glutathione S-Transferase - Yaqian Jin; Sheikh Arslan Sehgal; Faizul Hassan; Guiqin Liu (Animals, 2025)
Haemonchosis caused by the parasitic worm Haemonchus contortus is a major threat to cattle and other ruminants and imposes significant economic losses in the livestock industry. Different medications have been reported; however, these are not reliable now due to mass drug resistance. The current study investigates potential inhibitors of two H. contortus proteins: glutathione S-transferase (GST) and beta-tubulin isotype 1. GST helps the parasite to detoxify harmful substances, while beta-tubulin is essential for the cell division and structure. By using computational approaches, natural compounds were identified to inhibit the selected proteins. The 3D structures of GST and β-tubulin isotype 1 were prepared, and pharmacophore models were generated to search the Molport natural compound library. The lowest binding energy ranged from −6.7 to −10.4 Kcal/mol. Post-docking interactional analyses revealed that Glu45, Arg46, Cys126, Gln131, Lys252, Asn247, and Arg251 residues were the most common interacting residues in β-tubulin isotype 1. Similarly, in GST, Leu99, Asn100, Arg103, Lys107, Glu162, and Met163 were the most common interacting residues. In conclusion, extensive computational analyses including virtual screening, docking, and MD simulations revealed that the compound Molport-039-195-358 might have the ability to control haemonchosis by targeting GST and β-tubulin isotype 1. The in silico studies identified potent compounds by targeting GST and β-tubulin isotype 1 against Haemonchus contortus. The reported findings provide a foundation for the development of novel anthelmintic therapies.